PELAKSANAAN PEMBERIAN HAK MILIK ATAS TANAH NEGARA KEPADA MASYARAKAT (STUDI DI KANTOR BPN KABUPATEN LOMBOK UTARA) - Rina Rizqika Aolia; Wiwiek Wahyuningsih (Private Law, 2021)
The purpose of this study is to determine the implementation of granting ownership rights to State land in practice at the Land Office of North Lombok Regency and the obstacles and solutions in the implementation of granting ownership rights to the State land. The type of research used is empirical law using a normative approach and an empirical approach. The implementation of granting ownership rights to State land is regulated in the regulation of the State Minister for Agrarian Affairs / Head of the National Land Agency Number 9 of 1999 concerning procedures for obtaining and canceling rights to State land and management rights. In granting ownership rights to State land, there are several stages, starting from the requirements for the application for ownership rights, the requirements for granting ownership rights, measuring, granting ownership rights to State land and fulfilling the obligations to receive these rights. The Land Office should make more efforts to provide legal awareness to the public, especially regarding the importance of proof of ownership of land through counseling.